Investigating Risk-On Risk-Off Patterns in Global Financial Markets - Tročil, Jan (2014)
The aim of this thesis is to analyse the increased correlation within four major asset groups (Government Bonds, Equity Indices, Commodities and Currencies) from the beginning of Great Recession till July 2014. The effect of increased correlation is called Risk-On Risk-Off and is connected to problems, where investors struggle to create risk-oriented portfolios and instead minimalize loss. The methods analysing the correlations are Absolute Average Value Index (AAVI) and Heat-map analysis. The AAVI is transforming correlation matrix into a single number and investigating the intensity of correlations. The Heat-map is studying the relationship between any two assets. The results from this study were that the RORO effect was present during Great Recession with intensity never seen before and that in June 2014 the values are close to pre-recession levels.